Moral Values of Market economy in an Islamic System - Bakhiet, Hayat Abdallah (Journal of Economic, Administrative and Legal Sciences, 2021)
Under the scientific revolution, the internal market has seen insufficient to expand production. Capital and markets have become truly international. The free market economy needs many stops, to know its effects and dimensions on the citizen and his social values. The aim of the research is to clarify the essence of the Islamic economic system and to activate the system of moral values that it urged in the economic and other fields. Proving the failure of the positivist systems in achieving sustainable development, fighting poverty and preserving the environment. The study used the descriptive approach to list the concepts related to the topic and the comparative approach to clarify the difference between the values and ethics of the free market in the Islamic system and the positive economic systems. The result of the study shows that in an Islamic system the moral values are contradicted selfishness, exploitation and extravagance, and make man the goal of life because he derives his existence and value from his succession of God on earth. Among these values are respect for human dignity, justice and respect for nature. The study recommended the adoption of the Islamic economic system, in order to bring about a successful sustainable development that integrates material and spiritual factors. With the presence of some successful experiences to be a lesson of experience.